2012
DOI: 10.1016/s1353-8020(11)70016-5
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease: Molecular risk factors

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder second only to Alzheimer's disease. Diagnosis remains clinical, based on phenotypic patterns. In the last decade many attempts to develop early differential pre-clinical markers have been reported. In this presentation, the molecular risk factors that may link between the etiopathogenesis leading to PD and peripheral markers will be discussed. Genetic variation known to be involved in familial forms of PD will be shown to be linked to sporadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Following these findings, more specifically, the down-regulation of ALDH1A1 mRNA was found by our group using genomewide transcriptomic assay in SN from PD patients compared to controls (Grünblatt et al 2004). Following this report, many other groups could consistently confirm ALDH1A1 down-regulation in the SN of PD patients (Durrenberger et al 2012;Grünblatt 2012;Kotraiah et al 2013). In the last report by Kotraiah et al the analysis was extended to the various splice variants of ALDH1A1, which all showed similar down-regulation (Kotraiah et al 2013).…”
Section: Transcriptomic Alterationssupporting
confidence: 71%
“…Following these findings, more specifically, the down-regulation of ALDH1A1 mRNA was found by our group using genomewide transcriptomic assay in SN from PD patients compared to controls (Grünblatt et al 2004). Following this report, many other groups could consistently confirm ALDH1A1 down-regulation in the SN of PD patients (Durrenberger et al 2012;Grünblatt 2012;Kotraiah et al 2013). In the last report by Kotraiah et al the analysis was extended to the various splice variants of ALDH1A1, which all showed similar down-regulation (Kotraiah et al 2013).…”
Section: Transcriptomic Alterationssupporting
confidence: 71%
“…Not only will these biomarkers be useful for diagnosing the disease in affected persons, it will be useful for identifying family members or populations at risk, thus providing an opportunity to initiate neuroprotective therapy at an asymptomatic stage. Literatures have reported the transcription (RNA) profiles in peripheral blood samples might be of diagnostic value for estimating the risk of developing sporadic PD [ 16 , 22 ]. Mitochondrial dysfunction, reactive oxygen species (ROS), proteasome dysfunction and neuroinflammation are implicated in PD [ 23 26 ], as the mutations or changes of genes related with these processes, such as PINK1, Parkin, DJ-1, SNCA, UCHL1, LRRK2, TRIM24, MUL1 and USP30, are found to be widely present in PD [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various risk and protective factors of PD have been extensively investigated over several decades, however the etiology remains largely unclear [ 3 ]. There is a great interest in identifying at-risk individuals early, to potentially slow down or prevent neurodegeneration [ 4 ]. While genetic and familial environmental exposures are often cited to contribute to PD risk, lifestyle exposures such as smoking, coffee/tea and alcohol consumption have been the focus of research for several decades with varying and often conflicting results.…”
Section: Introductionmentioning
confidence: 99%